The Effect of Self-Concept and Family Environment on the Learning Outcomes of High School Students - Aspanizam, Aisy Alyna Binti; Ahmed, Ahmed Sagaff (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2024)
This study was motivated by the phenomenon of low learning outcomes among students in Islamic Religious Education, which ideally should demonstrate higher achievement since it is closely related to religious values and attitudes. This condition prompted the researcher to examine the influence of self-concept and family environment on students’ learning outcomes in Islamic Religious Education at the senior high school level. The study employed a quantitative approach with an associative method. The research population consisted of 497 students, from which 83 were selected as samples using a proportional stratified random sampling technique. Data were collected through questionnaires, and the analysis involved assumption testing and hypothesis testing using simple and multiple regression analyses. The results revealed that; i) self-concept had a positive and significant effect on students’ learning outcomes, with a regression coefficient of 0.203 and a contribution of 17.2%; ii) the family environment had a positive and significant effect, with a regression coefficient of 0.094 and a contribution of 4.4%; and iii) self-concept and family environment jointly had a positive and significant effect, with a coefficient of determination of 17.3%. These findings indicate that the more positive the self-concept and the stronger the family support, the higher the students’ learning outcomes in Islamic Religious Education. This study highlights the importance of synergy between internal psychological development and external family support in enhancing learning achievement and shaping students’ religious character.